AN INVESTIGATION OF INTERNAL LOGISTICS OF A LEAN BUS ASSEMBLY SYSTEM VIA SIMULATION: A CASE STUDY - Johnson, Aric (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
This study involves the internal logistics of a chosen bus assembly plant that follows a lean assembly process dictated by takt time production. The assembly system works according to a rigid sequential order of assembly of different models of buses, called the String of Pearls. The logistics department is responsible for supplying kitted components to assembly workstations for the right model at the right time. A simulation model was developed to study this assembly system, with an objective of finding the minimum number of kit carts for multiple production rates and kitting methods. The implementation of JIT kitting was the ultimate goal in this case. The research focused on a specific assembly plant and therefore, the numerical results are applicable to the selected plant only. However, some of the trends in the output may be generalized to any assembly plant of similar type.